2017
DOI: 10.1021/acscatal.6b03335
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Isoprene by Sequential Hydrogenation of Itaconic Acid and Dehydra-Decyclization of 3-Methyl-Tetrahydrofuran

Abstract: Catalytic hydrogenation of itaconic acid (obtained from glucose fermentation) yields 3-methyl-tetrahydrofuran (3-MTHF), which then undergoes catalytic dehydra-decyclization to isoprene. It is demonstrated that a one-pot cascade reaction converts itaconic acid to 3-MTHF at ∼80% yield with Pd−Re/C catalyst and 1000 psig H 2 . Subsequent gas-phase catalytic ring opening and dehydration of 3-MTHF with phosphorus-containing zeolites including P-BEA, P-MFI, and P-SPP (self-pillared pentasil) exhibits 90% selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 24 publications
7
103
0
Order By: Relevance
“…Myrcene and Far are both found in nature, but can also be produced by pyrolysis of β‐pinene and microbial pathways from glucose, respectively. Although, there are new bio‐based pathways to synthesize butadiene and isoprene, myrcene and Far are made up of multiple isoprene units, which can provide different rheological properties. It was shown that bottlebrush polymers with densely packed, long side chains improve elastic properties .…”
Section: Introductionmentioning
confidence: 99%
“…Myrcene and Far are both found in nature, but can also be produced by pyrolysis of β‐pinene and microbial pathways from glucose, respectively. Although, there are new bio‐based pathways to synthesize butadiene and isoprene, myrcene and Far are made up of multiple isoprene units, which can provide different rheological properties. It was shown that bottlebrush polymers with densely packed, long side chains improve elastic properties .…”
Section: Introductionmentioning
confidence: 99%
“…Even in cases where helium gas cylinders are used, it is possible to set up helium cylinder multi-packs in conjunction with manifolds for such equipment, enabling continuous operation for weeks without requiring replacement. Setting up liquid feed dosing using syringe pump/HPLC pumps remains manual but is usually quick; as pointed out before, for applications only requiring an initial estimation of product distributions, a significantly simpler version of this setup as a transient pulsed micro-reactor from our earlier works 26 , 27 can be utilized, which would barely require any manual intervention in setting up feeds, as the dosing is through the GC autosampler itself. Similarly, for chemistries utilizing light gases as feeds (e.g., methane activation, carbon dioxide valorization), it is possible to set up individual lines with separate mass flow controllers (MFCs), and such systems can run practically indefinitely for a given catalyst bed.…”
Section: Resultsmentioning
confidence: 99%
“…One straightforward implementation of low-cost automated micro-reactors with broad applicability among previously reported approaches is the pulsed-flow technique, which involves dosing a pulse of reactant over a catalytic material to study product distribution trends. This approach is readily integrated within a commercial GC, 26 , 27 , 28 , 29 , 30 , 31 , 32 but the transient nature of the technique limits kinetic parameter estimation. In addition, the product distributions under such transient conditions may vary from corresponding steady-state values.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is a promising and competitive route to convert biomass-derived feedstocks into isoprene via chemical processes. Itaconic acid from glucose [89] was employed as raw material by Abdelrahman [74]. Firstly, itaconic acid was converted into 3-methyl-tetrahydrofuran (3-MTHF) with a yield of about 80% in a liquid phase using Pd-Re/C as a catalyst.…”
Section: Synthesis Of Isoprenementioning
confidence: 99%